2022
DOI: 10.1002/cb.2116
|View full text |Cite
|
Sign up to set email alerts
|

The mere possession effect of shareable digital coupons: The mediating role of anticipated self‐enhancement

Abstract: Shareable digital coupons have emerged as a new marketing strategy. Prior literature on shareable coupons assumes that shareable coupons can play a role only after they have been shared with others. Surprisingly, we theorize that shareable coupons can come into play as early as when consumers merely possess them, even before consumers share them with others, an effect that precedes the effect of the actual coupon sharing. In this research, we show that the mere possession of shareable digital coupons (not nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Moreover, this effect is expected to be amplified among consumers with a high self‐enhancement need. Self‐enhancement need refers to the intrinsic motivation of individuals to cultivate and maintain a positive perception of themselves (Baumeister, 2010; Escalas & Bettman, 2003; Valenzuela et al, 2018; Zhang et al, 2023). These individuals attach heightened importance to the impression they present to others (Eisingerich et al, 2015; Sedikides & Strube, 1995), and thus, they are more likely to remain vigilant and react more negatively toward a brand's behavior if they perceive it as potentially damaging to their self‐image.…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this effect is expected to be amplified among consumers with a high self‐enhancement need. Self‐enhancement need refers to the intrinsic motivation of individuals to cultivate and maintain a positive perception of themselves (Baumeister, 2010; Escalas & Bettman, 2003; Valenzuela et al, 2018; Zhang et al, 2023). These individuals attach heightened importance to the impression they present to others (Eisingerich et al, 2015; Sedikides & Strube, 1995), and thus, they are more likely to remain vigilant and react more negatively toward a brand's behavior if they perceive it as potentially damaging to their self‐image.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…These relationships become instrumental for the consumers to reflect a particular image to others (Angelis et al, 2012; Eisingerich et al, 2015; Sedikides & Strube, 1995). Building on the tenets of social‐identity theory and self‐enhancement need (Baumeister, 2010; Escalas & Bettman, 2003; Shrauger, 1975; Tajfel & Turner, 1985; Valenzuela et al, 2018; Zhang et al, 2023), this study proposes that individuals seek to establish strong relationships with brands that align with their self‐concept and reinforce positive evaluations of themselves. Therefore, brand actions that dilute the brand's meaning may negatively impact consumers' self‐concept, especially among those who are highly connected to the brand.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, e-coupons provide price reductions to consumers who acquire and redeem them. Many studies have shown that consumer characteristics such as demographic variables [7,22], psychological variables [6,9,23,24] and social variables [25][26][27][28] may affect customers' e-coupon acquiring and using behaviors. Consumers are often required to provide retailers with their personal information [17] or even pay to acquire and use ecoupons before purchase [2].…”
Section: E-coupon-using Behaviorsmentioning
confidence: 99%
“…One such demographic cohort that has garnered attention in marketing circles is Generation Z, often referred to as digital natives. Generation Z individuals are characterized by their fluency and comfort with digital technologies (Zhang et al, 2023). They represent a critical target market for digital coupon campaigns due to their tech-savvy nature and reliance on technology for various aspects of their lives.…”
Section: Introductionmentioning
confidence: 99%